Analysis Of Profitability, Good Corporate Governance And Audit Quality On Audit Delay - Ni Kadek Ayu Trisnadewi; Ni Luh De Erik Trisnawati; Riana Dewi Kartika (Lembaga Riset dan Inovasi Al-Matani, 2023)
This study aims to determine the effect of financial performance on stock prices in This study aims to determine the Effect of Profitability, Good Corporate Goernance Structure, and Audit Quality on Audit Delay in Manufacturing companies on the Indonesia Stock Exchange (IDX) which provide audited financial report data by accessing and downloading the official website of the Indonesia Stock Exchange via the website www.idx. co.id. The sampling technique used in this study was carried out by purposive sampling. The population in this study were manufacturing companies listed on the Indonesia Stock Exchange (IDX) in 2018-2020. The total population that researchers used in this study were 168 companies. The data analysis technique used in this study starts from . Classical Assumptions Test. This study conducted normality, heteroscedasticity, and multicollinearity tests using the SPSS for windows version 25. After that, Descriptive Analysis was carried out. This study shows the results that the first hypothesis, namely profitability has a significant negative effect on audit delay. The second hypothesis is that the structure of good corporate governance has a significant negative effect on audit delay and has been verified. The third hypothesis is that audit quality has a significant negative effect on audit delay. Furthermore, the hypothesis proposed in this study, namely profitability, good corporate governance structure and audit quality have a significant effect on audit delay tested for truth.